Editorial - Neves, Pedro Soares (Street Art & Urban Creativity, 2024)
As for the Butterfly Effect, our actions resonate widely and far. A singular affordance or a city-wide tag, premeditated or not, conforms to our collective reality. But more specifically, is there something that occurs in Lisbon (and other places) that we can designate as a useful non-conformity with the norm? Taking this idea to the extreme, do our societal organizations serve as mere masks for the true anarchy of everyday life? In times of localized conflicts with global impact, from the nearly irrelevant comfort to life-threatening confrontations, what is the role of our material actions? In the realms of ideas or self-proposed solutions, what can we learn from our micro-actions? If there is indeed a common global phenomenon that emerges from mark-making as a life-standing condition, how can we interpret these marks for the sake of life? Can we generalize?